Pengaruh Sikap dan Pengalaman Kerja terhadap Intensi Kewirausahaan Pemuda (Studi di Kota Dobo) - Anmama, Ranny Orpha; Sinay, Francisca Riconita; Tupamahu, Fenri Abraham (Jurnal Pendidikan Ekonomi, 2023)
The growth of entrepreneurship among youth is a crucial factor in strengthening the regional economy, particularly in Dobo City, which possesses vast business opportunities. This study aims to analyze the influence of attitude and work experience on youth entrepreneurial intentions. A quantitative approach was employed, collecting data via questionnaires from 106 young entrepreneurs selected as samples. The data were analyzed using multiple regression to assess the contribution of each variable to entrepreneurial intention. The results indicate that a positive attitude and relevant work experience significantly affect entrepreneurial intentions among youth, both partially and simultaneously. The findings confirm that these factors are essential in shaping the readiness and willingness of young people to engage in entrepreneurship. The implications highlight the importance of fostering strong character and providing early work experience as strategies to increase entrepreneurial interest. Thus, focused training and development programs aimed at enhancing attitude and offering practical work experience are highly recommended to accelerate the growth of young entrepreneurs in the region